Photovoltaic hybrid boost converter fed switched reluctance motor drive - Ravi Kiran Dasari; Godwin Immanuel Dharmaraj (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Pollution from conventional transportation methods is a worrying factor. Electric vehicles are a viable option to reduce environmental pollution and to replace the conventional methods of using internal combustion (IC) engine based transportation system. renewable source driven electric vehicles (EV) opens up non-dependency on conventional energy sources. The renewable energy source (like photovoltaic system) insists on the switch mode converter to augment its voltage range. This paper presents a hybrid boost switch mode DC-DC converter to increase the voltage range of the photovoltaic (PV) system. The wheels of electric vehicle are coupled to switched reluctance motor (SRM). Closed-loop speed controlled SRM drives the wheels of EV. Asymmetrical converter feeds the excitation current to the coils of 6/4 pole current-controlled SRM. The proposed EV system is analyzed for fixed and variable torque with speed condition using MATLAB/SIMULINK software.